Öcsöd-Kováshalom, Ungarn. Forschungen zu Tell-Siedlungen und ihrer Umgebung in Ostungarn. Die Arbeiten der Jahre 2018 bis 2021 - Bánffy, Eszter; Rassmann, Knut; Füzesi, András; Raczky, Pál (e-Forschungsberichte des DAI, 2023)
The research of tell settlements coming from the first half of the 5th millennium BC go back to almost a century. Yet, earlier research was concentrated on the sites and barely on their perimeter. The new project of the RGK, in cooperation with the Eötvös Loránd (ELTE) University in Budapest and with the Hungarian National Museum, sets mainly these outskirts in focus. New data of non- or minimalinvasive surveay as well as small-sclae, targeted excavations will be compared with the results of earlier excavations, opening new avenues for so that a better understanding of social structure and networks within the late Neolithic Carpathian basin.